Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual Beli Online Melalui Platform Marketplace di Indonesia - Terania, Medi; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The growth of online transactions through marketplace platforms presents new challenges in terms of legal rights protection for customers. One of the primary issues that emerges is the imbalance between consumers and businesses, both in terms of access to information, resources, and legal channels. Many consumers in Indonesia are not fully aware of their legal rights, including the right to obtain correct and reliable information, the right to security, as well as the right to file a lawsuit if they suffer losses. This lack of understanding prevents many consumers from pursuing their cases through legal channels, even in cases of fraud. On the other hand, businesses and marketplace platforms usually possess an edge when it comes to accessing information, control of resources, and adequate legal support, which further widens the power gap between the two parties. This situation shows that access to justice for consumers, especially small consumers, continues to be minimal in the application of digital commerce in Indonesia. Active involvement from the government, consumer protection agencies, and platform providers is needed to build a more balanced legal protection system that is accessible to all elements of society.